2021
DOI: 10.1097/mcc.0000000000000906
|View full text |Cite
|
Sign up to set email alerts
|

Chest imaging in patients with acute respiratory failure because of coronavirus disease 2019

Abstract: Purpose of review This review aims to explore the different imaging modalities, such as chest radiography (CXR), computed tomography (CT), ultrasound, PET/CT scan, and MRI to describe the main features for the evaluation of the chest in COVID-19 patients with ARDS. Recent findings This article includes a systematic literature search, evidencing the different chest imaging modalities used in patients with ARDS from COVID-19. Literature evidences different possible approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Of the changes following chest CT scans, the most common imaging manifestation was ground-glass opacity (64.2%). Various studies have similarly reported that GGO is the most common change on CT images, followed by consolidation [ 14 , 15 , 16 , 17 , 18 , 19 ]. Pleural effusion, along with pericardial effusion, lymphadenopathy, cavitation, and pneumothorax are among the less common but potential features found as the disease progresses [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the changes following chest CT scans, the most common imaging manifestation was ground-glass opacity (64.2%). Various studies have similarly reported that GGO is the most common change on CT images, followed by consolidation [ 14 , 15 , 16 , 17 , 18 , 19 ]. Pleural effusion, along with pericardial effusion, lymphadenopathy, cavitation, and pneumothorax are among the less common but potential features found as the disease progresses [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…LUS score has been used as a value to monitor ARDS evolution and the effects of mechanical ventilation on lung aeration. Data regarding diagnostic performance of LUS score demonstrated high accuracy (93.3%), sensitivity (100.0%), and specificity (92.9%) for severe lung lesions, confirming its usefulness in the diagnosis and monitoring of critical COVID-19 patients [72].…”
Section: Scores and Protocols Proposed On Lus And Pocusmentioning
confidence: 67%
“…Similarly, authors have reported role of inflammatory markers in association with CT findings. [42][43][44][45] Very few cases (2.10%) cases in Evolving phenotype were shown less than four-fold raised inflammatory markers. Rationale for this would be lesser ongoing inflammation in presence of early GGOs in COVID-19 pneumonia which is indicator of controlled inflammation.…”
Section: Evolved and Evolving Patterns In Study Cases And Its Correla...mentioning
confidence: 96%